TELAAH ULANG MANHAJ TAHLILI (TAFSIR ANALISIS) - Anieg, Muhammad (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2014)
Tafsir is the main instrument in an attempt to answer the problems of theÂ people, who must soon discovered the concept or theory. This departs from theÂ question that is often uttered by Hassan Hanafi: " hal ladainÄ naáº“ariyah fi â€™lTafsÄ«r?" This is an Islamic thinker anxiety on the theory and methodology ofÂ interpretation that is less classical touches many social problems. From hereÂ arises the methods, including taá¸¥lÄ«lÄ« (analysis). Taá¸¥lÄ«lÄ« method (analysis) is toÂ interpret the verses of the Qur'an to describe all aspects contained in the versesthat are interpreted and explained the meanings contained therein in accordanceÂ with the expertise and inclination commentators interpret these verses. TheÂ main purpose taá¸¥lÄ«lÄ« method is to lay the foundations for a rational understanding of the miracle of the Qur'an, something which is not considered an urgentÂ need for Muslims today. Because it is necessary to develop a method of interpretation because this method produces the idea that diverse and fragmented.Keywoard: al-Qurâ€™an, manhaj, taá¸¥lÄ«lÄ«, tafsir, analisis=1*18&('18*$'(888('?8821B(*8&(?*2>7('12=8&(?(2?7(B&2'$18122192k(*(8&(929(?82*8&(2*E&1(?*81=*2'8&(c$(1828&812=8($88(*(>11=6}&77oN*&=07.=1r*â€ }&1117'98&%(*â€¢(828&(8&(2*'(8&2272)2=8(*?*(8828&8 17(11 97119782$9&(1'1297 ?*2>7('1E*2'&(*(*1(18&('(8&2197$)8Z7r7r711EZ7r7r'(8&27111828(*?*(88&(k(*1(12=8&(/$*â€¢82(19*>(771?(981928(8&(k(*1(18&8*(8(*?*(8((â€¢?7(8&('()1928(8&(*(992*9(B8& 8&( (â€¢?(*81( 9782 92''(882*1 8(*?*(8 8&(1( k(*1(1E &('?$*?21(8Z7r7r'(8&218278&(=2$821=2**827$(*18.)2=8&('*97(2=8&(/$*â€¢12'(8&)B&9&128921(*($*)(8((=2* $17'182E(9$1(81(9(11*82(k(72?'(8&22=8(*.?*(882>(9$1(8&1'(8&2?*2$9(18&((8&8k(*1(=*)'(8(E8$968$96 7./$*0'&@8Z7r7r8=1*711